The Israel-Palestine Conflict: A Legal and Ethical Analysis of War Crimes, Humanitarian Violations, and the Erosion of International Law - Hariz, Nafhan; Hafidz, Muhammad; Hafiz, Naufal; Pamungkas, Rifcy (Candidate: Jurnal Sains Politik, 2025)
The Israel-Palestine conflict, rooted in historical territorial disputes rather than solely religious differences, has evolved into one of the most complex and protracted conflicts in modern international relations. This study adopts a qualitative descriptive approach to critically examine the conflict through the lens of Just War Theory and International Humanitarian Law (IHL). Focusing on recent escalations, the paper analyzes attacks on civilian infrastructure, the conduct of hostilities, and the protection of non-combatants as mandated under the Geneva Conventions and the Rome Statute of the International Criminal Court. The findings reveal systematic violations of IHL, particularly in the principles of proportionality and distinction, with substantial evidence indicating the commission of potential war crimes. The analysis underscores that both Israeli military actions and Hamas operations have compromised the fundamental tenets of humanitarian law, exacerbated humanitarian crises and undermining the credibility of international legal frameworks. Furthermore, the paper highlights the long-term implications of these violations, including the risk of global erosion of humanitarian norms, the destabilization of regional peace efforts, and the entrenchment of cycles of violence and displacement. The research calls for stricter enforcement of international law, impartial investigations into alleged war crimes, and the reaffirmation of the universality of humanitarian principles to restore legitimacy to the global legal order. Addressing the conflict requires more than ceasefires; it demands a comprehensive legal, moral, and political commitment to upholding the rights and dignity of all affected populations.